Hepaticoplasty prevents cholangitis after pancreaticoduodenectomy in patients with small bile ducts. (November 2016) - Hiyoshi, Masahide; Wada, Takashi; Tsuchimochi, Yuki; Hamada, Takeomi; Yano, Koichi; Imamura, Naoya; Fujii, Yoshiro; Nanashima, Atsushi
Abstract: Background: To reduce cholangitis after pancreaticoduodenectomy (PD), we perform 'hepaticoplasty', in which the left side of the bile duct is cut to widen the diameter of the bile duct wall before hepaticojejunostomy. The aim of this study was to clarify the usefulness of hepaticoplasty to reduce cholangitis after PD. Methods: From January 2002 through December 2010, 161 patients underwent PD and were enrolled in this study. Patient demographics, surgical factors, and clinical and biochemical parameters were evaluated to examine the factors predictive of cholangitis after PD and confirm the usefulness of hepaticoplasty. Results: Cholangitis after PD occurred in 13 patients (8.1%). Multivariate analysis revealed that the ratio of the postoperative bile duct diameter to that before surgery was the only independent risk factor for cholangitis after PD (p = 0.0012). In the small bile duct group, in which the diameter was ≤15 mm before surgery (n = 99), hepaticoplasty reduced the narrowing of the bile duct after PD, and no cholangitis occurred. There were no complications related to hepaticoplasty. Conclusions: The ratio of postoperative reduction of the bile duct diameter to that before surgery was found to be the only risk factor for cholangitis after PD. Patients with a small bile duct of ≤15 mm in diameter preoperatively might benefit from hepaticoplasty to widen the bile duct diameter and prevent cholangitis after PD. Highlights: We examined the predictive factors and usefulness of hepaticoplasty to prevent cholangitis after pancreaticoduodenectomy. The ratio of postooperative reduction of the bile duct diameter after surgery is an important concern in cholangitis. Hepaticoplasty was safe, and it might be useful in the prevention of cholangitis after pancreaticoduodenectomy.